Bom Retiro: the formation of an urban landscape - Santos, Márcio P. (GEOUSP Espaço e Tempo (Online), 1998)
We have attem pted to offer an exam ple of how w ebs act in space, through a review concerning the history of production of a fraction of the urban sp ace of the city of São Paulo, the district of Bom Retiro. This area, along the second half of the 19th century and beginning of the 20th, had its "rural landscape" changed into a "urban landscape" due to the im plantation of m aterial and social w ebs. These w ebs are created below dem and of local social dynam ics associated to the transition and em erging of power-owning social classes. This article is a small essay based on our m aster degree work, in execution at the Geography D epartm ent of the University of São Paulo